1979
DOI: 10.1128/jvi.30.1.21-31.1979
|View full text |Cite
|
Sign up to set email alerts
|

In vitro translation of adenovirus type 12-specific mRNA isolated from infected and transformed cells

Abstract: The early and late gene products of human adenovirus type 12 (Ad12), as well as the viral proteins synthesized in an Ad12-transformed cell line, were identified by translation of viral mRNA in an in vitro protein-synthesizing system. Cytoplasmic RNA was isolated from permissive KB or nonpermissive BHK cells infected with Ad12 and from Ad12-transformed HA12/7 cells. Virus-specific RNA was selected by hybridization to Ad12 DNA covalently bound to cellulose. Viral RNA was then translated in a fractionated rabbit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Below the figure a scale in nucleotides serves as a frame of reference. functions on the genome by previously published DNA-RNA hybridization and cell-free translation experiments (19,20,30).…”
Section: Discussionmentioning
confidence: 99%
“…Below the figure a scale in nucleotides serves as a frame of reference. functions on the genome by previously published DNA-RNA hybridization and cell-free translation experiments (19,20,30).…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that the protection experiments performed in this study allowed the detection of VA RNAs in productively infected cells. In the abortively Adl2-infected BHK-21 cells, Adl2-specific VA RNA was not produced, even though most of the El functions of Adl2 DNA were transcribed (10,16). It is conceivable that in addition to the ElA functions (3,12), host cell functions are required to activate the polymerase III-mediated transcription of the Adl2-specific VA RNA.…”
Section: Notes 3539mentioning
confidence: 99%
“…There is a total block of Adl2 DNA replication in this host system (7,9,11), although virions are taken up into the cytoplasm and viral DNA enters the nucleus and can be integrated into the host genome (6,8). In hamster cells, most of the early viral functions are transcribed into mRNA (16)(17)(18) which can be expressed in a cell-free transcription system (10). In contrast, transcription of the late Adl2 genes in hamster cells cannot be detected (13,14,17).…”
mentioning
confidence: 99%
“…It should be noted, however, that the early functions of Adl2 DNA can be efficiently expressed in hamster cells (14,15,23,28,34). Hence, the trans-activation by Ad2 or Ad5 functions appears to be required mainly for the expression of the late Adl2 functions and for the replication of Adl2 DNA.…”
Section: Fig S Expression Of Latementioning
confidence: 99%
“…Adl2 virions do infect hamster cells; the viral DNA reaches the nucleus, and a portion of the parental viral DNA molecules is integrated into the host genome (9,11). The early functions of Adl2 DNA are expressed (27,28,30), whereas RNA sequences homologous to the late Adl2 genes cannot be detected in hamster cells (14,28). It could be demonstrated by in vitro translation of hybrid-selected RNAs that, in Adl2-infected BHK-21 cells, all of the early viral mRNAs are synthesized as in productively infected cells, except for a 34,000molecular-weight (34K) protein from the ElA region of Adl2 DNA (14).…”
mentioning
confidence: 99%